Une génération entre deux crises : jeunes précaires et indignés dans l’Espagne actuelle - Alicia Fernández García (Cahiers de Civilisation Espagnole Contemporaine)
On the occasion of the 10th anniversary of the Spanish Indignados movement, this contribution will attempt to provide an analysis of its contributions and its consequences. To achieve this, she will focus first on the indignant discourse in order to study the extent to which it still marks the political and media agenda in Spain. Then, she will study the repercussions and traces of the movement within youth and at the social and political level so as to better understand the ruptures and continuities.